#TITLE_ALTERNATIVE# - ADRIANTO SETIADI (NIM 13202135), EVAN
Orthogonal Frequency Division Multiplexing (OFDM) is a wireless communication system where high speed serial data rate are transmitted by n-orthogonal subcarrier. Wireless channel with its characterisics which cause signal degradation is the reason of implementing channel estimation. By implementing channel estimation, receiver can predict the channel characteristics, so the signal's amplitude and phase can be compensated. Pilot Symbol Assisted Modulation (PSAM) is a channel estimation technique where an amount of pilot signal are inserted with specific arrangement. On this final project, channel characteristics are analyzed by applying comb type and block type pilot arrangement. Also, by applying linear interpolation and second order interpolation channel estimator. The simulation result indicate the channel estimation using second order channel estimator in doppler frequency 97,2 Hz for block type reach BER 3,29.10-3 on Eb/N0 40 dB. Meanwhile, comb type only 3,93.10-3.